Analysis of Marketing Strategies for MSMEs in Facing Global Competition - Iskak, Jamaludin (Jujurnal Publisher, 2025)
This study aims to analyze the marketing strategies employed by micro, small, and medium enterprises (MSMEs) to enhance their competitiveness in global markets. Using a qualitative approach and a literature review method, the study synthesizes relevant research, reports, and case studies to identify key strategies for MSMEs in the context of global competition. The findings reveal that MSMEs increasingly adopt a hybrid marketing strategy, integrating both digital and traditional methods to reach international markets effectively. Digital marketing tools, such as social media and SEO, are vital for expanding online presence and engaging with global consumers, while traditional marketing strategies, including trade fairs and direct selling, remain essential for building trust and fostering long-term business relationships. The study highlights that MSMEs face significant challenges, including resource constraints and cultural barriers, but these can be mitigated through a combination of strategic marketing approaches and external support from governments and institutions. The research suggests that MSMEs can improve their global competitiveness by leveraging the synergies of digital and traditional marketing methods. Further research is recommended to explore the long-term impact of hybrid strategies and the potential role of emerging technologies in enhancing MSME marketing efforts in a globalized economy.